Navigating Interstitial Lung Disease: Overcoming Diagnostic Obstacles and Advancing Treatment Strategies (Bangladesh Journal of Child Health, 2025)
Childhood interstitial lung disease (ChILD) encompasses a diverse range of rare respiratory disorders in children that can result in significant morbidity and mortality. The lung interstitium are connective tissue space, between the alveoli and the small blood vessels that surround the alveoli, that provide support to the components of the respiratory tract, such as bronchial division up to alveoli, blood vessels, lymphatics etc. Interstitial lung diseases are conditions that affect these structures, leading to inflammation and scarring of lung tissue. This impact hinders lung expansion, gaseous exchange, and can ultimately result in a restrictive lung disease. Symptoms of respiratory distress may develop gradually and might be subtle, highlighting the importance of a comprehensive clinical evaluation including thorough clinical history and physical examination. The cause of ChILD is often unknown, with symptoms resembling more common conditions like pneumonia or asthma, making accurate diagnosis challenging. Genetic testing, bronchoalveolar lavage, or lung biopsy may be needed for confirmation. Treatment involves supportive care and anti-inflammatory, immunosuppressive, or anti-fibrotic medications. The delayed diagnosis can potentially lead to chronic respiratory failure. This review aims to provide key findings to assist in clinical evaluation and proper diagnostic decision-making, especially for children in developing countries like Bangladesh where specialized respiratory centers may not be available.BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 128-135